Early Adjuvant Medication With the mTOR Inhibitor Sirolimus in a Preterm Neonate With Compressive Cystic Lymphatic Malformation - Honnorat, Marion; Viremouneix, Loïc; Ayari, Sonia; Guibaud, Laurent; Coste, Karen; Claris, Olivier; Butin, Marine (Frontiers in Pediatrics, 2020)
Cystic lymphatic malformations result from an abnormal embryological development of the lymphatic structures. Here we report on a case of a preterm female baby, born at 34 weeks of gestation, with a voluminous cervicofacial cystic lymphatic malformation responsible for an airway obstruction. An mTOR inhibitor, sirolimus, was started from the first day of life, and was combined with iterative sclerotherapy procedures. This case illustrates a safe and successful early administration of sirolimus in a preterm neonate.